Impact of Self-Efficacy and Work Flexibility on Employee Performance in Cikarang Manufacturing Companies - Zakiyah Putri; Muhammad Sapruwan (DEAL: International Journal of Economics and Business, 2025)
This study examines the influence of self-efficacy and work flexibility on employee performance in the contemporary work environment. The study aims to analyze how employees' confidence in their abilities (self-efficacy) combined with flexible work arrangements affects overall work performance. Using a quantitative approach, data was collected from 78 employee respondents across a variety of industries through standardized questionnaires. The sample size was determined to ensure adequate representation and statistical validity in examining the relationships between variables. Data analysis was conducted using Smart-PLS, which allows for robust structural equation modeling (SEM) to evaluate complex relationships between self-efficacy, work flexibility, and employee performance. The results showed a significant positive correlation between self-efficacy and employee performance, while work flexibility showed a moderate positive relationship of performance outcomes. Furthermore, the interaction between self-efficacy and work flexibility showed a synergistic effect, indicating that employees with high self-efficacy in particular thrived when given flexible work arrangements. These findings contribute to understanding how personal psychological resources and organizational policies can be optimized to improve workplace productivity and employee satisfaction.